Fish! For Life: A Remarkable Way to Achieve Your Dreams - Stephen C. Lundin, John Christensen & Harry Paul
Millions of people around the world have already used the bestselling FISH books and videos to improve the way they work. Now] the authors turn their attention to helping readers apply the FISH! Philosophy to life's daily challenges in the home] such as stress] weight control] personal finance] and much more.